Tin‐doped bismuth dendrites for highly efficient electrocatalytic reduction of CO2 by using bipolar membrane in ultrathin liquid reactor. Issue 6 (2nd August 2022) - Peng, Luwei; Chen, Changsheng; He, Ruinan; Xu, Nengneng; Qiao, Jinli; Lin, Zezhou; Zhu, Ye; Huang, Haitao
Abstract: Electrochemical CO2 reduction reaction is a promising protocol to achieve a carbon‐neutral cycle. Herein, we report a general strategy to regulate the growth of Sn‐doped Bi dendritic electrode with numerous labyrinthine and porous channels to provide abundant tips, edges, terraces, and low coordination sites for efficient conversion of CO2 into formate. As a result, the dendritic Sn‐doped Bi achieves a high partial current density (30 mA/cm 2 ), a high Faradic efficiency of formate (95.5%), and a long‐term durability (>60 h). Most remarkably, the self‐made bipolar membrane can effectually prohibit the cross‐over of formate from cathode to anode and the oxidization of small organic molecules in anode can promote the production of formate on both anode and cathode sides. This work provides helpful insights to the design of electrocatalysts, bipolar membrane, and ultrathin liquid reactor. Abstract : The dendritic Sn‐doped Bi with numerous labyrinthine and porous channels provide abundant tips, edges, terraces and low coordination sites for efficient conversion of CO2 into formate. Thus, the dendritic Sn‐doped Bi electrode can achieve a considerably high partial current density (30 mA cm −2 ), Faradic efficiency of formate (95.55%) and long‐term durability (>60 h).